Di Balik Status Anak: Kritik terhadap Pertimbangan Hakim dalam Menjatuhkan Putusan terhadap Anak Pelaku Pelecehan Seksual (LEGAL DIALOGICA, 2026)
This study aims to examine the legal considerations of judges in rendering decisions against children as perpetrators of sexual harassment and to analyze the criminal liability imposed on children in such cases. This research employs a normative legal research method with a literature study as the data collection technique. The legal materials obtained are then analyzed and described descriptively to derive the meaning of legal rules used as references in resolving legal issues. The results of the study indicate that in cases of sexual harassment involving children, judicial considerations balance the protection of the rights of the child perpetrator with the judge's goal of facilitating the child’s rehabilitation while ensuring that the child victim receives adequate protection. Criminal liability for child perpetrators prioritizes recovery and rehabilitation over harsh punishment, with sanctions focused on helping the child reform their behavior. The study recommends that judges, in sentencing child offenders, should base their decisions on considerations that provide benefits for the child, as children represent the future of the nation. Law enforcement officials are also encouraged to conduct educational and outreach efforts in the community regarding the issue of child sexual harassment, in order to reduce the incidence of such crimes